Renato Rizzi - Paola Ardizzola; Joanna Grądzka (Vitruvio: International Journal of Architectural Technology and Sustainability)
Full Professor in Architectural Design at the Instituto Universitario di Architettura (IUAV) in Venice, he carries out an intense intellectual activity by connecting teaching, theory, research, and practice. Prize of the Italian Presidency of the Republic for architecture 2017, he has delivered seminars and lectures in some of the main universities including Harvard, UIC Chicago, ETH, etc. From 1984 to 1992 he collaborated with Peter Eisenman, New York, on the projects Romeo and Juliet, Verona (1986, Stone Lion, III Architecture Biennale of Venice), La Villette Park, Paris (1986), Monte Paschi, Siena (1988), etc. Among the main international projects: Great Egyptian Museum, Cairo (2002, third prize); MOMA Warsaw (2007, Honorable Mention); John Paul II Center, Krakow (2007, special mention); Torre della Ricerca, Padua (2008, fourth prize, in collaboration with Peter Eisenman); Museum of Judaism, Ferrara (2010, Special Mention). Main projects completed: Ghiaie Sports Area, Trento (1984-1998); Fortunato Depero Museum of Futurism, Rovereto (1992-2008); Gdańsk Shakespearean Theater (2004-2013). His projects are published in the main international magazines such as Casabella, Domus, Architectural Review, Detail, and have been exhibited at the Venice Biennale (1984, 1985, 1996, 2002, 2010 and 2016), Triennale di Milano, Accademia di San Luca, etc. Awards: Fritz Höger, Berlin, 2017; Architizer A, Belgium, 2016; Iconic Award, Monaco DB, 2015; Gold Medal, Milan, 2015, 2009; Golden Compass, Milan, 2015, 2011; Council of Europe, Landscape Award, 2009. Some significant publications: Il Cosmo della Bildung, Mimesis 2016; Unexpected Parma, MUP 2013; The Daìmon of Architecture, Mimesis 2014; John Hejduk, Incarnatio, Marsilio 2010; The Divine of the Landscape, Marsilio 2008; John Hejduk BRONX, Manual in verse, Mimesis 2020. He recently founded in Venice the Nuova Scuola Architettura, a free school that focuses on the urgency of a new (heretical) gaze at Architecture, a necessity which derives from the cultural abyss of our time. The Accademia Nazionale di San Luca in Rome is currently paying a tribute to his oeuvre in a grand exhibition of gypsum models and maquettes titled “eden-eden. Renato Rizzi”, which can be visited until March third, 2023.